Evaluación de tratamientos silviculturales aplicados al manejo de tres bloques de bosque secundario ubicados en Coope San Juan, Aguas Zarcas, San Carlos, Costa Rica, 2002 - Córdoba-Alvarado, Danny (Instituto Tecnológico de Costa Rica, 2002)
The practice was developed in the Finca de la Cooperativa de Autogestión San Juan R.L, located in the Region North Huetar of Costa Rica. We worked in three blocks of secundary forest with 23 years of age, in which forestry treatments were applied in 2000. A forest harvesting was carried out in the three blocks, combined with lianas cutting in Block II. The objective of this work was to make an evaluation of the forestry treatments applied to the three blocks of secondary forest. This evaluation was carried out using permanent plots of samplin to quantify the response of the remaining mass. Temporary plots of regenation and the methodology of visit to stumps, to evaluate the impact of the forest harvest.
Proyecto de Graduación (Bachillerato en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2002.
Keywords: Cosechas; Regeneración de bosques; Potencial; Zonas protegidas; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry